The Role of Muhammadyah Volunteers in Helping Micro Businesses in Sirenja Subdistrict, Donggala Regency, Central Sulawesi Province to Stay in the Middle of the Covid-19 Pandemic Crisis - Abdul Hanif; Fery Fery; Cahyaning Raheni (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
This study aims to determine the efforts made by MDMC Volunteers in helping micro-businesses to survive amid the Covid-19 Pandemic Crisis. This type of research is descriptive qualitative, data collection methods are observation studies, interviews, documentation, and data analysis techniques. The results of the study show that the role of MDMC volunteers in helping micro-businesses to survive the Covid-19 Pandemic has had a very positive effect, apart from providing a capital injection of 4 million rupiahs for each micro business, micro-entrepreneurs are also equipped with health facilities in preventing covid-19 in the form of a place for washing hands using a tap, a collection bucket, and a chair as a holder for washing hands.